PREDICTION OF RAINFALL IN DKI JAKARTA PROVINCE BASED ON THE FOURIER SERIES ESTIMATOR - Zidni Ilmatun Nurrohmah; Diana Ulya; Qumadha Zainal Abidin; Syifaun Nadhiro; Nur Chamidah (Jurnal Statistika Universitas Muhammadiyah Semarang, 2022)
Abstract: Rainfall is the height of rainwater in a rain gauge on a flat place that does not seep and flow, where rainfall is measured in millimeters (mm). This study aims to estimate and model the rainfall for DKI Jakarta Province from January 2016 to December 2021 using the Fourier series estimation. Based on the results of the study, a model with a minimum GCV value of 21909,4, at the 7th ???? 43,78972. This model shows that the predictor variable can explain the diversity of response variables by 94,14%.